Churchill's war lab : code-breakers, scientists, and the mavericks Churchill led to victory - Downing, Taylor (Overlook Press, 2011)
Analyzes the role of Churchill's passion for military history in shaping his wartime innovations and strategies, offering insight into his unique leadership style and patronization of radical new ideas to enable unprecedented technological advances.